(untitled) - Woodson, R. Dodge (New York, 2005)
Be a Successful Building Contractor will give you the business savvy you need to set up and manage a profit-making enterprise. The book will help you define your business requirements-find desirable building lots-build on speculation-computerize your operations-track financial transactions-hire top-notch employees-and much more
Keywords: Contractors,Building trades; Management